Deposition of Cu films for laser mirror by partially ionized beam deposition - Koh, Seok-Keum; Yoon, Young-Soo; Kim, Ki-Hwan; Jang, Hong-Gui; Jung, Hyung-Jin (Materials Research Society Symposium - Proceedings, 1995)
Partially ionized beam deposition of Cu thin films on glass at room temperature were carried out to fabricate Cu laser mirrors with good structural and reflectance properties. At a constant film thickness of 600 angstrom, the grain size of as-grown Cu films increased with acceleration voltage, and there was no indication of defects such as cracks and/or large pores in the film surface as shown in scanning electron microscopy images. Root-mean-square(Rms) surface roughnesses of the films with thicknesses of 600 angstrom were measured by atomic force microscopy. Rms surface roughness increased when acceleration voltage increased from 0 kV to 2 kV, but decreased at the acceleration voltage of 3 kV. Rms surface roughness of the film grown at 4 kV, however, increased again. At the acceleration voltage of 3 kV, reflectance of the films increased with the film thickness until 600 angstrom and decreased at the film thickness of 800 angstrom. The reflectance results showed that the Cu film deposited at 3 kV had higher reflectance than that of others. Our results suggest that it is possible to grow the Cu film with good structural and optical properties on glass substrate at room temperature by partially ionized beam deposition.